2015
DOI: 10.1080/13540602.2015.1055423
|View full text |Cite
|
Sign up to set email alerts
|

One country, two cultures – a multi-perspective view on Israeli chemistry teachers’ beliefs about teaching and learning

Abstract: This paper presents a study focusing on differences in Israeli Jewish and Arab chemistry teachers' beliefs regarding teaching and learning of chemistry in the upper secondary schools. Israel is a country experiencing the problems of diverse cultural orientation of its inhabitants but applying the same educational system to its diverse cultural sectors. Education includes the same curriculum in chemistry for both the Israeli Jewish and Arab cultural sectors as well as final examinations (matriculation) set cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 51 publications
0
15
0
6
Order By: Relevance
“…In accordance with a previous literature survey and conceptual framework (Dkeidek et al 2011(Dkeidek et al , 2012Markic et al 2016; Gross and Issa 2020) and the Research Authority for Measurement and Evaluation (2019), the current study aimed to examine the teaching practices science teachers from the Arab community in Israel use when they teach science. Because teaching practices affect students' development of scientific skills and scientific literacy, understanding these practices is necessary in order to construct a suitable intervention program that leads to future change.…”
Section: Science Education In the Arab Sector In Israel-ethnic Perspectivesmentioning
confidence: 99%
“…In accordance with a previous literature survey and conceptual framework (Dkeidek et al 2011(Dkeidek et al , 2012Markic et al 2016; Gross and Issa 2020) and the Research Authority for Measurement and Evaluation (2019), the current study aimed to examine the teaching practices science teachers from the Arab community in Israel use when they teach science. Because teaching practices affect students' development of scientific skills and scientific literacy, understanding these practices is necessary in order to construct a suitable intervention program that leads to future change.…”
Section: Science Education In the Arab Sector In Israel-ethnic Perspectivesmentioning
confidence: 99%
“…More specifically, the professional development programs and models that I developed, implemented, and researchered over the last 30 years in the Jewish and Arab sectors in Israel, as well as in USA, Georgia, Germany, Singapore, Taiwan, Estonia, Japan, Tanzania, and other countries are based on research findings related to my topics of practice and the research that I mentioned above, as well as inquiry-based skills, e.g., argumentation, asking questions, postulating (Blonder, Rap, Mamlok-Naaman and Hofstein, 2015;Cai and Mamlok-Naaman (Eds. )., 2020), laboratory skills (Mamlok-Naaman and Barnea, 2012), and cultural aspects (Dkeidek, Mamlok-Namman and Hofstein, 2011;Markic, et al, 2016;Mamlok-Naaman and Taitelbaum, 2019).…”
Section: Professional Development Of Chemistry Teachersmentioning
confidence: 99%
“…Bryk et al [7] identified professional communities, along with a work culture oriented [8], toward improvement and access to professional development, with elements of "professional capacity" associated with improvements measured in primary school achievement in Chicago over a period of 6 years in the 1990s. A recent study by Kraft and Papay [9] reinforced this important insight.…”
Section: Teachers' Professional Learning Communities (Plcs)-theoreticmentioning
confidence: 99%